Evolutionary Relationships and Divergence of KNOTTED1-Like Family Genes Involved in Salt Tolerance and Development in Cotton (Gossypium hirsutum L.) - Zhang, Xiaohong; Zhao, Junjie; Wu, Xiangyuan; Hu, Genhai; Fan, Shuli; Ma, Qifeng (Frontiers in Plant Science, 2021)
The KNOX (KNOTTED1-like homeobox) transcription factors play an important role in leaf, shoot apical meristem and seed development and respond to biotic and abiotic stresses. In this study, we analyzed the diversity and evolutionary history of the KNOX gene family in the genome of tetraploid cotton (Gossypium hirsutum). Forty-four putative KNOX genes were identified. All KNOX genes from seven higher plant species were classified into KNOXI, KNOXII, and KNATM clades based on a phylogenetic analysis. Chromosomal localization and collinearity analysis suggested that whole-genome duplication and a polyploidization event contributed to the expansion of the cotton KNOX gene family. Analyses of expression profiles revealed that the GhKNOX genes likely responded to diverse stresses and were involved in cotton growth developmental processes. Silencing of GhKNOX2 enhanced the salt tolerance of cotton seedlings, whereas silencing of GhKNOX10 and GhKNOX14 reduced seedling tolerance to salt stress. Silencing of GhSTM3 influenced the cotton flowering time and plant development. These findings clarify the evolution of the cotton KNOX gene family and provide a foundation for future functional studies of KNOX proteins in cotton growth and development and response to abiotic stresses.